Стратегічні напрямки розвитку ринку олійної продукції в контексті повоєнного відновлення та євроінтеграції - Антонюк, П. О.; Antonyuk, P. O. (Запоріжжя : Видавничий дім «Гельветика», 2025)
UA: Дослідження присвячене аналізу перспектив розвитку ринку олійної продукції України в контексті повоєнного відновлення та євроінтеграційних процесів. Обґрунтовано стратегічні напрями модернізації цього ринку. Сформовано рекомендації щодо інноваційного оновлення аграрного сектору, розвитку інфраструктури та логістичних ланцюгів, механізмів фінансування і державної підтримки. Виявлено необхідність адаптації виробничих процесів до європейських стандартів та регуляцій, що сприятиме розширенню доступу до ринків ЄС. Окрему увагу приділено збільшенню частки олійних культур у структурі сільськогосподарського виробництва та забезпеченню сталого розвитку, зокрема впровадженню екологічних практик. Розглянуто питання підвищення конкурентоспроможності української продукції на світових ринках через виробництво продукції з високою доданою вартістю та формування позитивного іміджу на міжнародній арені. /// EN: The study is devoted to the analysis of the prospects for the development of the oil products market of Ukraine in the context of post-war recovery and European integration processes. Strategic directions for the modernization of this market are substantiated. Particular attention is paid to the issues of rebuilding the production infrastructure after military destruction, increasing the investment attractiveness of the sector, developing processing technologies and ensuring compliance with European Union standards. The prospects for the integration of Ukrainian producers into global supply chains are outlined, the role of state support and international cooperation in stimulating exports is considered. The article proposes a set of measures aimed at restoring and developing the oil products market, increasing its competitiveness and ensuring sustainable economic growth of the industry in the context of European integration. The results of the study may be useful for representatives of agribusiness, government agencies and experts dealing with issues of economic development and international trade. Recommendations are formulated regarding the innovative renewal of the agricultural sector, the development of infrastructure and logistics chains, financing mechanisms and state support. The need to adapt production processes to European standards and regulations was identified, which will contribute to expanding access to EU markets. A set of measures aimed at restoring and developing the oilseed market, increasing its competitiveness and ensuring sustainable economic growth of the industry in the context of European integration was proposed.Particular attention is paid to increasing the share of oilseeds in the structure of agricultural production and ensuring sustainable development, in particular the implementation of environmental practices. The role of sustainable development and environmental standards in shaping the future market for oilseed products is separately considered. The need to introduce modern production methods that minimize environmental impact, in particular energy efficiency and waste processing technologies, is emphasized. Such an approach will contribute not only to compliance with European requirements, but also to strengthening the position of Ukrainian products in the global food system. The issue of increasing the competitiveness of Ukrainian products in world markets through the production of products with high added value and the formation of a positive image in the international arena is considered.
Strategic directions of development of the oil products market in the context of post-war reconstruction and european integration
Keywords: стратегія; напрямки розвитку; ринок; ринок олії; продукція; воєнне відновлення; повоєнне відновлення; євроінтеграція; strategy; development directions; market; oil market; products; war recovery; post-war recovery; European integration